2022
DOI: 10.1186/s12891-022-05337-2
|View full text |Cite
|
Sign up to set email alerts
|

Disc repositioning by open suturing vs. mini-screw anchor: stability analysis when combined with orthognathic surgery for hypoplastic condyles

Abstract: Background Disc repositioning by Mitek anchors for anterior disc displacement (ADD) combined with orthognathic surgery gained more stable results than when disc repositioning was not performed. But for hypoplastic condyles, the implantation of Mitek anchors may cause condylar resorption. A new disc repositioning technique that sutures the disc to the posterior articular capsule through open incision avoids the implantation of the metal equipment, but the stability when combined with orthognathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We used the method as we previously reported to assess jaw stability after simultaneous TMJ and orthognathic surgery, which includes jaw position, rotation, contralateral healthy condyle position, and surface bone remodeling [ 18 ]. The results showed that at the last follow-up, jaw and condylar position were stable, and no obvious bone resorption happened on the condylar bone surface (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the method as we previously reported to assess jaw stability after simultaneous TMJ and orthognathic surgery, which includes jaw position, rotation, contralateral healthy condyle position, and surface bone remodeling [ 18 ]. The results showed that at the last follow-up, jaw and condylar position were stable, and no obvious bone resorption happened on the condylar bone surface (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The remodeling of the surface bone was compared by superimposition comparison using surface-best-fit registration according to non-surgical areas of the mandible between T1 and T2. The comparison threshold was set as 2 mm [ 18 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%